PATRIOTIC OUTLOOK AND ANTI-NATIONAL PHENOMENA IN BORIS GRINCHENKO’S WORKS FOR CHILDREN - Вовк, Олена; Іваночко, Ганна (SWorldJournal, 2025)
The article is devoted to the theory of national revival of B. Grinchenko as the author’s specification of the nation-wide theory of ethno-cultural rooting; the basic methodological parameters of the axiological approach to the interpretation of the phen